A biologic definition of Burkitt's lymphoma from transcriptional and genomic profiling. - Hummel, M.; Bentink, S.; Berger, H.; Klapper, W.; Wessendorf, S.; Barth, T. F.; Bernd, H. W.; Cogliatti, S. B.; Dierlamm, J.; Feller, A. C.; Hansmann, M. L.; Haralambieva, E.; et al. (N Engl J Med, 2006)
BACKGROUND: The distinction between Burkitt's lymphoma and diffuse large-B-cell lymphoma is unclear. We used transcriptional and genomic profiling to define Burkitt's lymphoma more precisely and to distinguish subgroups in other types of mature aggressive B-cell lymphomas. METHODS: We performed gene-expression profiling using Affymetrix U133A GeneChips with RNA from 220 mature aggressive B-cell lymphomas, including a core group of 8 Burkitt's lymphomas that met all World Health Organization (WHO) criteria. A molecular signature for Burkitt's lymphoma was generated, and chromosomal abnormalities were detected with interphase fluorescence in situ hybridization and array-based comparative genomic hybridization. RESULTS: We used the molecular signature for Burkitt's lymphoma to identify 44 cases: 11 had the morphologic features of diffuse large-B-cell lymphomas, 4 were unclassifiable mature aggressive B-cell lymphomas, and 29 had a classic or atypical Burkitt's morphologic appearance. Also, five did not have a detectable IG-myc Burkitt's translocation, whereas the others contained an IG-myc fusion, mostly in simple karyotypes. Of the 176 lymphomas without the molecular signature for Burkitt's lymphoma, 155 were diffuse large-B-cell lymphomas. Of these 155 cases, 21 percent had a chromosomal breakpoint at the myc locus associated with complex chromosomal changes and an unfavorable clinical course. CONCLUSIONS: Our molecular definition of Burkitt's lymphoma clarifies and extends the spectrum of the WHO criteria for Burkitt's lymphoma. In mature aggressive B-cell lymphomas without a gene signature for Burkitt's lymphoma, chromosomal breakpoints at the myc locus were associated with an adverse clinical outcome.
Keywords: Algorithms; Burkitt Lymphoma/diagnosis/*genetics/pathology; DNA, Neoplasm/analysis; Diagnosis, Differential; Female; Follow-Up Studies; *Gene Expression; *Gene Expression Profiling; Genes, Immunoglobulin; Genes, bcl-2; Genes, myc; Humans; Lymphoma, B-Cell/classification/diagnosis/*genetics/mortality; Male; Middle Aged; Oligonucleotide Array Sequence Analysis; Oncogene Proteins, Fusion/genetics; Prognosis; RNA, Neoplasm/analysis; Survival Rate; Transcription, Genetic; Translocation, Genetic